Pseudopyxis heterophylla subsp. monilirhizoma (Rubiaceae, tribe Paederieae), a new combination from Zhejiang of China, based on morphological trait analysis - YE Lixin; ZHOU Yingying; LIU Lingjuan; CHEN Weijie; LIU Shenglong; ZHENG Chaozong; JIN Xiaofeng (浙江大学学报. 农业与生命科学版)
Pseudopyxis Miq., a genus distributed in eastern China and Japan, comprises three species, in which Pseudopyxis monilirhizoma Tao Chen is endemic to China. The variation analysis of the diagnostic characters among these three species of Pseudopyxis was carried out. Based on principal coordinate analysis (PCoA) of eighteen morphological characters, the individuals of P. depressa were separated distinctly from P. heterophylla+P. monilirhizoma, whereas the separation between P. heterophylla and P. monilirhizoma was not clear. The observations of stem indumentum and seed micromorphology showed the difference between P. depressa and P. heterophylla + P. monilirhizoma, while that of P. heterophylla and P. monilirhizoma was consistent. In case of the observations of stem indumentum and seed micromorphology and PCoA of morphological characters, P. monilirhizoma is consequently combined as a subspecies of P. heterophylla (Miq.) Maxim., and the combination of P. heterophylla subsp. monilirhizoma (Tao Chen) L. X. Ye, C. Z. Zheng & X. F. Jin is proposed.